Ligand‐induced μ opioid receptor internalization in enteric neurons following chronic treatment with the opiate fentanyl. Issue 6 (29th March 2013) - Anselmi, Laura; Jaramillo, Ingrid; Palacios, Michelle; Huynh, Jennifer; Sternini, Catia
<x xml:space="preserve">Abstract</x> Morphine differs from most opiates its poor ability to internalize μ opioid receptors (μORs). However, chronic treatment with morphine produces adaptational changes at the dynamin level, which enhance the efficiency of acute morphine stimulation to promote μOR internalization in enteric neurons. This study tested the effect of chronic treatment with fentanyl, a μOR‐internalizing agonist, on ligand‐induced endocytosis and the expression of the intracellular trafficking proteins, dynamin and β‐arrestin, in enteric neurons using organotypic cultures of the guinea pig ileum. In enteric neurons from guinea pigs chronically treated with fentanyl, μOR immunoreactivity was predominantly at the cell surface after acute exposure to morphine with a low level of μOR translocation, slightly higher than in neurons from naïve animals. This internalization was not due to morphine's direct effect, because it was also observed in neurons exposed to medium alone. By contrast, D‐Ala2‐N‐Me‐Phe4‐Gly‐ol5‐enkephalin (DAMGO), a potent μOR‐internalizing agonist, induced pronounced and rapid μOR endocytosis in enteric neurons from animals chronically treated with fentanyl or from naïve animals. Chronic fentanyl treatment did not alter dynamin or β‐arrestin expression. These findings indicate that prolonged activation of μORs with an internalizing agonist such as fentanyl does not enhance the ability of acute morphine to trigger μOR endocytosis or induce changes in intracellular trafficking proteins, as observed with prolonged activation of μORs with a poorly internalizing agonist such as morphine. Cellular adaptations induced by chronic opiate treatment might be ligand dependent and vary with the agonist efficiency to induce receptor internalization. © 2013 Wiley Periodicals, Inc.